SIAS: Sensory Impairment Assistive Software - C, Supriya; Mahesh, Janavi; Karan; K S, Keerthana; R, Navyashree (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
SIAS – Sensory Impairment Assistive Software, presents an innovative application of YOLO (You Only Look Once), and CNN (Convolutional Neural Network). Through Python-based deep learning techniques, the system leverages YOLO’s speed and accuracy to identify objects within a live camera feed, providing vocal announcements to the user. Furthermore, it offers a few additional features, which include gesture-to-speech conversion to facilitate communication between the physically challenged, Text-to-speech conversion, and Image Processing. This proposes an innovative communication system framework for deaf, dumb and blind people within a single compact device.